Selection of patients with symptomatic vagal-induced sinus node dysfunction: Who will be the best candidate for cardioneuroablation? - Cai, Simin; Zheng, Lihui; Yao, Yan (Frontiers in Physiology, 2023)
Sinus node dysfunction is a multifaceted disorder with variable manifestations, the prevalence of which increases with age. In a specific group of patients, excessive vagal activity may be the sole cause for this condition. These patients are characterized as having recurrent daytime symptoms attributed to bradyarrhythmia, no evidence of organic sinus node lesions, cardiac vagal overactivation, and are non-elderly. For sinus node dysfunction patients, a permanent pacemaker implantation appears to be the ultimate solution, although it is not an etiological treatment. Cardioneuroablation is a promising emerging therapy that can fundamentally eliminate symptoms in a highly selective sub-set of sinus node dysfunction patients by cardiac vagal nerve denervation. Denervation with ablation for vagal-induced sinus node dysfunction can effectively improve sinus bradycardia and reduce syncope. To date, guidelines for selection of suitable candidates for cardioneuroablation remain lacking. The primary objective of this study was to distinguish the nature of abnormal sinus node function and to find methods for quantifying vagal tone. Clear selection criteria could help physicians in identification of patients with autonomic imbalance, thereby maximizing patient benefits and the success rate of cardioneuroablations.